GAMBARAN JUMLAH LEUKOSIT DARAH PADA PASIEN APPENDISITIS AKUT DI RSUD dr. H. MOCH. ANSARI SALEH BANJARMASIN - Perdani, Rizki; Falahi, Dwi Noor; Pratiwi, Wulan; Alfarizi, Hafiz (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Acute appendicitis is inflammation appendix which can cause leukocytosis. Leukocytosis is a condition of increasing the number of leukocytes in the body. Leukocytosis occurs due to a non-specific immune response to inflammation that occurs. This study aims to determine the description of the number of blood leukocytes in acute appendicitis patients based on age and complications findings at RSUD Dr. H. Moch. Ansari Saleh Banjarmasin in 2023. This type of research is quantitative descriptive research with a cross sectional design. The sampling technique used a total sampling technique and obtained 35 samples. The results showed that 85.9% of acute appendicitis patients had leukocytosis, 11.4% had normal leukocyte counts and 2.9% had leukopenia. Based on age group, non-productive age patients were found to have 11,4% leukocytosis results. Meanwhile, in productive age, leukocytosis results were found to be 74,3%. Based on the type of appendicitis, patients with simple appendicitis were found to have a leukocytosis rate of 25,7%, while patients with complicated appendicitis were found to have a leukocytosis rate of 60%. So it can be concluded that there is an increase in the number of blood leukocytes in acute appendicitis patients based on age and findings of complications.